Growth performance and rhizospheric traits of peach (Prunus persica) in response to mycorrhization on replant versus non-replant soil - ZHANG, ZE-ZHI; SRIVASTAVA, A K; WU, QIANG-SHENG; LI, GUO-HUAI (The Indian Journal of Agricultural Sciences, 2015)
Replant disease is considered as a major bottleneck towards improved production of stone fruits such as peach (Prunus persica L. Batsch). Studies were carried out to investigate the effects of inoculation with an arbuscular mycorrhizal fungus (AMF), Funneliformis mosseae on the plant and rhizosphere related parameters on replant versus non-replant soil. In replant soil with AMF treatment, root mycorrhizal colonization was reduced by 48.2% over nonreplant soil. This was well translated through significant decrease in growth attributing characters like plant height, stem diameter, leaf number, and shoot and root dry weight on replant soil, but upon AMF inoculation, a complete reversal of these responses was observed, coupled with an increase in total chlorophyll concentration. Mycorrhizosphere quality indicators, viz. easily extractable glomalin-related soil protein, total glomalin-related soil protein and soil organic carbon concentration were significantly higher in mycorrhizosphere than non-mycorrhizosphere under both replant as well as non-replant soil. These glomalin-related soil proteins in combination with soil organic carbon cemented the water-stable aggregates at 2.00-4.00 and 1.00-2.00 mm size fractions, eventually leading to higher mean weight diameter in mycorrhizosphere. Profiling of soil enzyme activities showed higher catalase and peroxidase activity but lower polyphenol oxidase activity in mycorrhizosphere compared to non-mycorrhizosphere of replant soil. Our results suggested that inoculation with AMF negated the major ill effects of replant disease in peach.